Institutionalized Hypocrisy: sex, Money and Law - Kurczewski, Jacek (Oñati Socio-Legal Series, 2018)
This paper draws on analysis by social historians ranging from the late Middle Ages and Renaissance in France to recent administrative history in Poland to illustrate basic contradictions in Western thought about sexuality. These have resulted over time in policies which range from prohibition of sex work to tolerance of the need to meet physical needs accompanied by an appreciation of the financial profits to be obtained by the state as well as the individual, combined with abhorrence of female adultery. The paper closes with original data on current public attitudes towards the impact on reputation of a range of behaviours in Poland, including sexual activities, and finds a high level of agreement about the damaging impact on reputation of not sexwork itself but of living off the proceeds of sexwork.